THE CRIMINALIZATION OF MARITAL RAPE IN INDIA: A DISTANT DREAM - Anushka, (PEOPLE: International Journal of Social Sciences, 2020)
As per Indian Penal Code, 1860 (Sec.375) “Rape” is an offence whereby a man has sexual intercourse with a woman without her consent or when the consent is obtained through fraud, deceitful means or when the woman is of unsound mind or intoxicated. On one side where this section protects the women by providing strong punishment which would act as a deterrence, on the other hand the same section explicitly removes “Marital Rape” from the ambit of it and does not define it as rape, making women nothing but helpless sufferers at the hands of their spouses. Rape is a clear violation of human rights and the relationship between the sufferer and the perpetrator cannot be used as a defense in cases of rape under any circumstance. The argument that the Honorable Court puts forth is that criminalizing marital rape would destabilize the institution of marriage, this shows the presence of innate social misogyny present in our society which has led to exploitation of women at different stages of life. The exception clause of Sec. 375 is very evidently giving an upper hand to the husband and constant consent to sexual intercourse to which the wife has no option but to submit. This article is an attempt to expose the shortcomings and fallacies in the criminal justice system of India with regard to marital rape.